Biotechnological advances and applications of human pluripotent stem cell-derived heart models - Muniyandi, Priyadharshni; O’Hern, Colin; Popa, Mirel Adrian; Aguirre, Aitor (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, significant biotechnological advancements have been made in engineering human cardiac tissues and organ-like models. This field of research is crucial for both basic and translational research due to cardiovascular disease being the leading cause of death in the developed world. Additionally, drug-associated cardiotoxicity poses a major challenge for drug development in the pharmaceutical and biotechnological industries. Progress in threedimensional cell culture and microfluidic devices has enabled the generation of human cardiac models that faithfully recapitulate key aspects of human physiology. In this review, we will discuss 3D pluripotent stem cell (PSC)-models of the human heart, such as engineered heart tissues and organoids, and their applications in disease modeling and drug screening.